Gibson gets library post (Raton Range Raton, NM, 1984)
This article is about Vida Hollis Gibson of Cimarron being promoted to Direct the state's Regional Libraries.
Newspaper article + Photograph of the Cimarron Bookmobile
Mater List Item # 1
File location is in the New Mexico File Cabinets
Keywords: Gibso, Vida Hollis; Montoya, Edward "Corky"; New Mexico State Library; Cimarron Library; Bookmobiles; Libraries; Library Directors; Work Promotions; Santa Fe, New Mexico; Cimarron, New Mexico